SEXUAL VIOLENCE AND ITS DIMENSIONS IN TURKISH NOVEL - Nurullah ULUTAŞ (Fırat University, 2019)
Considered as a perverse behavioral pattern in almost every society, sexual violence is defined as to impose sexual words, psychological pressure, physical attack, intimidation, forceful sexual intercourse on a person who is unconscious or does not consent to such activities. Although "libido", also known as sexual energy, is the most important and positive function of human organism; it has been a factor for various crimes according to both psychology and penal law; and led people to crime since early times. The perception of sexuality as a preference related to freedom rather than a moral problem has been spreading with modernization period. I